Structural behavior of precast ultra-high Performance Fiber Reinforced Concrete (UHPFRC) cantilever retaining walls: part I - analysis and design procedures and Environmental Impact Calculations (EIC) - Nematollahi, Behzad; Voo, Yen Lei; Muhammad Rashid, Raizal Saifulnaz (Springer, 2014)
Ultra-high Performance Fiber Reinforced Concrete (UHPFRC) is a new generation of cementitious based construction material developed in the mid 1990s that its unique characteristics such as high durability and impermeability, negligible shrinkage/creep and high impact resistance lead to almost maintenance free and direct enhancement of the life-span of a structure. UHPFRC is an ecofriendly and environmentally green construction material which has the capacity to compete not only with conventional Reinforced Concrete (RC) or prestressed concrete design, but it is also able to compete with conventional steel design. This paper is presented in two parts. The first part (Part I) of this paper presents the analysis and design procedures of the precast UHPFRC cantilever retaining walls as a sustainable alternative approach to conventional precast RC cantilever retaining walls. Further, the Environmental Impact Calculations (EIC) of the precast UHPFRC cantilever retaining walls were compared against the conventional precast RC cantilever retaining walls as the benchmark. The second part (Part II) of this paper evaluates the reliability of the precast UHPFRC cantilever retaining walls through experimental tests on full scale UHPFRC wall specimens. The EIC results proved that cantilever retaining walls fabricated from UHPFRC are generally more environmentally sustainable than those built of the conventional RC with respect to the reduction of CO2 emissions, Embodied Energy (EE) and Global Warming Potential (GWP). Finally, advantages of the precast UHPFRC cantilever retaining walls versus the conventional precast RC walls were presented.